Porównanie wpływu internetowych i tradycyjnych form reklam na konsumentów sklepów kosmetycznych w Polsce - Mackiewicz, Natalia (Wydawnictwo Uniwersytetu Wrocławskiego, 2024)
The present work was written on the basis of secondary research, the analysis of available statistical data and reports on advertising and the cosmetics industry. In addition, primary research was carried out to compare the impact of online and traditional advertising on consumers of cosmetic stores in Poland. The survey was conducted on a sample of 314 respondents, where 280 were qualified for the survey, in November and December 2023. The respondents said that the most encouraging form of advertising is the one that appears in social media such as Facebook, Instagram, Tik Tok and etc. In addition, as many as 71% of respondents answered that online advertising encourages them to buy a cosmetic that they did not intend to buy. In the case of traditional advertising, it was only 35%. As for the attitude of respondents to the presented classification of advertising, internet advertising is much more positively perceived — 20 percent more answers than in the case of traditional advertising (definitely positive attitude or rather positive attitude).
Keywords: marketing communication; online advertising; traditional advertising; cosmetics industry